Effects of low-dose alcohol exposure in adolescence on subsequent alcohol drinking in adulthood in a rat model of depression. (26th November 2021) - Siska, Filip; Amchova, Petra; Kuruczova, Daniela; Tizabi, Yousef; Ruda-Kucerova, Jana
Abstract: Objective: Adolescence drinking and subsequent development of alcohol use disorder (AUD) is a worldwide health concern. In particular, mood dysregulation or early alcohol exposure can be the cause of heavy drinking in some individuals or a consequence of heavy drinking in others. Methods: This study investigated the effects of voluntary alcohol intake during adolescence, i.e. continuous 10% alcohol access between postnatal days (PND) 29 to 43 and olfactory bulbectomy (OBX) model of depression (performed on PND 59) on alcohol drinking in Wistar rats during adulthood (PND 80–120, intermittent 20% alcohol access). In addition, the effect of NBQX, an AMPA/kainate receptor antagonist (5 mg/kg, IP) on spontaneous alcohol consumption was examined. Results: Rats exposed to 10% alcohol during adolescence exhibited a lower 20% alcohol intake in the intermittent paradigm during adulthood, while the OBX-induced phenotype did not exert a significant effect on the drinking behaviour. NBQX exerted a transient reduction on alcohol intake in the OBX rats. Conclusions: Our results indicate that exposure to alcohol during adolescence can affect alcohol drinking in adulthood and that further exploration of AMPA and/or kainate receptor antagonists in co-morbid alcoholism-depression is warranted.